Shading screens for the improvement of the night time climate of unheated greenhouses - Montero, J. I.; Muñoz, P.; Sánchez-Guerrero, M. C.; Medrano, E.; Piscia, D.; Lorenzo, P. (Spanish Journal of Agricultural Research, 2013)
The objective of this work was to study the effect of shading screens, normally used during the day for cooling purposes, on the night-time climate of unheated greenhouses. For this purpose, first a number of experimental measurements were taken during cold nights to characterise the greenhouse climate both with and without an aluminised external screen. Secondly a Computational Fluid Dynamic (CFD) model of greenhouse was developed. After validation of the model by comparison with experimental data, the model was used to simulate the greenhouse climate for different sky conditions ranging from cloudless to overcast nights. Simulations were performed for a greenhouse with internal and external shading screens and for the same greenhouse without screens. Experimental results showed the positive effect of an external shading screen, whose use increased night-time temperature and reduced the risk of thermal inversion. Its effect was much stronger under clear sky conditions. The CFD model supported this conclusion and provided a detailed explanation of the temperature behaviour of all the greenhouse types considered. CFD simulations proved that an aluminised screen placed inside the greenhouse at gutter height gave the greatest thermal increase. Therefore, external or internal screens can help to increase the sustainability of greenhouse production in areas with mild winter climates by enhancing the use of solar energy stored in the greenhouse soil during the previous day and released at night-time.